Two Adjacent cis-Regulatory Elements Are Required for Ecdysone Response of Ecdysone Receptor (EcR) B1 Transcription - Shirai, Hiroyuki; Kamimura, Manabu; Yamaguchi, Junichi; Imanishi, Shigeo; Kojima, Tetsuya; Fujiwara, Haruhiko (PLOS ONE, 2012)
Three distinct classes of nuclear receptors, EcR, E75, and HR3, are key regulators in the ecdysone-inducible gene activation cascade in insects. The transcription of these genes is induced by ecdysone (20E) differently, although the detailed mechanisms underlying their responses to 20E are largely unknown. We identified ecdysone response elements (EcREs) present in the promoters of genes coding BmEcR-B1, BmE75-A, and BHR3-B isoforms from Bombyx mori employing luciferase reporter assays in an ecdysteroid-responsive cultured cell line, NIAS-Bm-aff3 (aff3). The EcRE of BmEcR-B1 at −2800 comprises of two adjacent elements separated by 5 bp, E1 (15 bp) and E2 (21 bp), both of which are required for the 20E response. Further analysis using electrophoretic mobility shift assays showed that E1 binds to the EcR/USP heterodimer and that E2 may bind to the E-box (CACGTG) binding factor such as bHLH protein. The unique E1+E2-type EcRE is also detected in the promoter upstream regions of EcR-B1 from seven lepidopteran species studied. In contrast, both a 20 bp EcRE identified in the promoter of BmE75-A and a 18 bp EcRE identified in the BHR3-B promoter, contained only E1-type EcR/USP binding element but the E2 type element was not in the promoter regions of these genes. The combination of presence of the E2 element or other cis-regulatory elements in promoter regions explains the different 20E response of each class of nuclear receptor genes. Furthermore, the E1+E2 structure for EcR-B1 can be involved in a possible cross-talk between ecdysteroid and other regulatory pathways.